Partisipasi Perempuan dalam Politik Perspektif Pendidikan Islam dan Gender - Suriadi Suriadi; Adnan Adnan; Jayadi Jayadi; Susilawati Susilawati; Mursidin Mursidin (Al-Ulum, 2018)
Islamic teachings essentially give great attention and honorable position to women. Politics in Islam known as as-siyasah are all human activities related to the settlement of various conflicts and creating security for society. While the leader of a person who has the skills and advantages, especially the skills or advantages in one area so he is able to influence other people to jointly perform certain activities for the achievement of one or several purposes. The opening of a widespread democratic system in Indonesia provides a good opportunity for the development of national politics. One of the indicators of the passage of a democratic political system and to measure the level of public participation in the political field, so the involvement of citizens becomes an absolute requirement for a nation that wants to build with the concept of democracy. Citizen involvement here is interpreted as a comprehensive engagement without distinction between the sexes of both men and women.